2017
DOI: 10.3324/haematol.2017.170928
|View full text |Cite
|
Sign up to set email alerts
|

CD56 bright natural killer regulatory cells in filgrastim primed donor blood or marrow products regulate chronic graft- versus -host disease: the Canadian Blood and Marrow Transplant Group randomized 0601 study results

Abstract: Randomized trials have conclusively shown higher rates of chronic graft-versus-host disease with filgrastim-stimulated apheresis peripheral blood as a donor source than unstimulated bone marrow. The Canadian Blood and Marrow Transplant Group conducted a phase 3 study of adults who received either filgrastim-stimulated apheresis peripheral blood or filgrastim-stimulated bone marrow from human leukocyte antigen-identical sibling donors. Because all donors received the identical filgrastim dosing schedule, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…13 Recently, a controlled study was undertaken evaluating the impact of stem cell source on the development of GVHD by assessing an array of immune subsets in filgrastimprimed donor products. 7 It was reported that lower levels of CD56 bright NK cells and interferon γ-producing CD4 cells resulted in a higher rate of cGVHD. Moreover, only one of these two immune subsets, a low level of CD56 bright NK cells, was also associated with the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Recently, a controlled study was undertaken evaluating the impact of stem cell source on the development of GVHD by assessing an array of immune subsets in filgrastimprimed donor products. 7 It was reported that lower levels of CD56 bright NK cells and interferon γ-producing CD4 cells resulted in a higher rate of cGVHD. Moreover, only one of these two immune subsets, a low level of CD56 bright NK cells, was also associated with the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 32 patients referred for ECP were enrolled and treated for a median of 7 months (interquartile range [IQR] [4][5][6][7][8][9][10][11][12][13][14]. Eleven patients with aGVHD (3 late-onset cases) and 21 with cGVHD (including 5 overlap syndrome cases) were recruited.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various subsets of NK cells play speci ic functions in the development and manipulation of GVHD. Examples include: (1) NKG2A + NK cells play a crucial role during early stages of GVHD following HSCT; (2) NKG2Cexpressing NK cells have a direct role in the early control of CMV reactivation after allogeneic HSCT; (3) c-Kit -CD 27 -CD11b + NK cell population is capable of signi icantly dimishing GVHD in the setting of fully mismatched allogeneic HSCT by supporting GVL effects whilst providing protection against the development of GVHD; (4) CD56 bright NK regulatory cells have been shown to have a much stronger impact on ilgrastimstimulated PB apheresis products than on ilgrastimstimulated BM products as lower proportions of CD56 bright NK regulatory cells result in higher rate of chronic GVHD seen in ilgrastim-stimulated PB apheresis; (5) iNK cell dose in allogeneic grafts is associated with signi icant improvement in GVHD and GVHD-free progression-free survival; (6) failure to reconstitute iNK cells following allogeneic HSCT is associated with higher risk of primary disease relapse; (7) low doses of adoptively transferred donor CD4 + iNK cells protect from GVHD while preserving GVT effects as these cells inhibit proliferation of alloreactive T cells and promote robust expansion of donor T regs; and (8) higher doses of CD4 -iNKT cells in PB stem cell allografts are associated with protection from acute GVHD [21,22,121,[124][125][126][127].…”
Section: The Role Of Nk Cells In Gvt/gvl and Gvhdmentioning
confidence: 99%
“…Four studies associated a decrease in CD58bright NK cells with the development of cGVHD [41,7274]. In one of the studies, CXCR3 + CD56 bright NK cells inversely correlated with CXCL10 as a significant biomarker panel for the diagnosis of cGVHD [41].…”
Section: Useful Cgvhd Biomarkersmentioning
confidence: 99%